PERANAN WAKAF DALAM PEMBANGUNAN EKONOMI UMAT ISLAM DAN APLIKASINYA DI MALAYSIA - Ab Rahman, Asmak (Jurnal Syariah, 2009)
Waqf is a form of charity with special features that has permanence and continuity. The beneficiaries can benefit from the waqf property for years, generations or even centuries. The ownership of waqf is withdrawn from the owner and returned to Allah for the benefit of His subjects to whom the property has been bequeathed. Waqf is a form of worship to Allah and has significant contribution to economic development as it plays an important role as wealth redistribution mechanism. In common tradition, properties given out for waqf purpose are namely mosque, land for Muslim cemeteries, business premises, agriculture lands, religious schools, etc. In the modern times, majority of Muslim scholars accept cash waqf, share of waqf, waqf of shares and takaful waqf as form of waqfs. This article aims to discuss the role of waqf in achieving the hike in economic development focusing on the human welfare among the Malaysian society. Waqf plays a vital role in poverty alleviation, health services, education, orphanage centre, mosques and residences for the needy society.